Functionalization of selenium nanoparticles with olive polyphenols – impact on toxicity and antioxidative activity - Galić Emerik; Radić Kristina; Golub Nikolina; Mlinar Jakov; Čepo Dubravka Vitali; Vinković Tomislav (Acta Pharmaceutica)
Selenium nanoparticles (SeNPs) represent novel selenium (Se) formulation characterized by improved biocompatibility and a wider therapeutic range in comparison to inorganic Se. The aim of this work was to investigate the possibilities of functionalization of SeNPs with olive pomace extract (OPE), rich in health-promoting polyphenols, and to obtain innovative forms of nutraceuticals. Cytotoxic and antioxidative activities of four types of SeNPs (polyvinylpyrrolidone stabilized (PVP SeNPs), polysorbate stabilized (PS SeNPs), polyvinylpyrrolidone stabilized and functionalized using OPE (f PVP SeNPs) and polysorbate stabilized and functionalized using OPE (f PS SeNPs) were investigated. SeNPs showed lower toxicity on human hepatocellular carcinoma (HepG2) and human colorectal adenocarcinoma (Caco2) cells compared to selenite. Functionalization with polyphenols significantly improved their direct antiradical (f PVP SeNPs: 24.4 ± 1.84 and f PS SeNPs: 30.9 ± 2.47 mg TE/mmol Se) and reducing properties (f PVP SeNPs: 50 ± 3.16 and f PS SeNPs: 53.6 ± 3.22 mg GAE/mmol) compared to non-functionalized SeNPs. The significant impact of tested SeNPs on intracellular antioxidative mechanisms has been observed and it was dependent on both cell type and physico-chemical properties of SeNPs, indicating the complexity of involved mechanisms.